2021
DOI: 10.1101/2021.03.26.437204
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Rapid response of nitrogen cycling gene transcription to labile carbon amendments in a soil microbial community

Abstract: Episodic inputs of labile carbon (C) to soil can rapidly stimulate nitrogen (N) immobilization by soil microorganisms. However, the transcriptional patterns that underlie this process remain unclear. In order to better understand the regulation of N cycling in soil microbial communities, we conducted a 48 h laboratory incubation with an agricultural soil where we stimulated the uptake of inorganic N by amending the soil with glucose. We analyzed the metagenome and metatranscriptome of the microbial communities… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 87 publications
(105 reference statements)
0
2
0
Order By: Relevance
“…The decreased copy number of functional genes of transcription, folding, classification and degradation, replication and repair and translation and so on may be correlated with the improvement in disease resistance in G. elata Bl. f. glauca by JMG [65][66][67]. These results indicated that JMG improves soil microbial metabolic functions of G. elata Bl.…”
Section: Discussionmentioning
confidence: 64%
“…The decreased copy number of functional genes of transcription, folding, classification and degradation, replication and repair and translation and so on may be correlated with the improvement in disease resistance in G. elata Bl. f. glauca by JMG [65][66][67]. These results indicated that JMG improves soil microbial metabolic functions of G. elata Bl.…”
Section: Discussionmentioning
confidence: 64%
“…5, A and B, and 9C). Genes encoding organic nitrogen mineralization ( gudB , gdh , gdhD , and GLUD1_2 ) are also known to carry out the same reaction in reverse order, i.e., generating amino acid glutamate from NH 4 + ( 39 ), therefore confounding its influence on bioavailable N generation. At the same time, the significant up-regulation of DNRA in the P-VI phase also cannot be ignored.…”
Section: Discussionmentioning
confidence: 99%